Respuesta :

Answer:

(A)

Step-by-step explanation:

Use the method: swap x for y and solve for y:

[tex]y=\frac{5x}{3}+5\rightarrow\\x=\frac{5y}{3}+5\\3(x-5)=5y\\\frac{3(x-5)}{5}=y=f^{-1}(x)[/tex]

The last expression is the inverse function and matches the answer (A).

The inverse of the function f(x) is Option (A) [tex]f^{-1}(x) = \frac{3(x - 5)}{5}[/tex]

Finding the inverse of a function f(x) -

To find the inverse of any function, we follow some steps which are -

  • First substitute the value of f(x) as y and represent the same equation.
  • Then we find the value of x making y as the dependent variable.  
  • After that we just replace the variable y by x and x by inverse function and therefore find the inverse function of f(x) .

Thus following the same steps in the question,

Given  [tex]f(x) = \frac{5x}{3} + 5[/tex]

⇒ [tex]y = \frac{5x}{3} + 5[/tex]

⇒ [tex]y - 5 = \frac{5x}{3}[/tex]

⇒ [tex]3(y - 5) = 5x[/tex]

∴ [tex]x = \frac{3(y - 5)}{5}[/tex]

Replacing the variables in the last step ,

∴ [tex]f^{-1}(x) = \frac{3(x - 5)}{5}[/tex]    which is Option (A)

To learn more about inverse function, refer -

https://brainly.com/question/11735394

#SPJ2